Postprocedure Intravenous Patient-Controlled Analgesia Compared to Epidural Patient-Controlled Analgesia Use after Uterine Fibroid Embolization: A Clinical Audit - Tran-Harding, Karen N. (Anesth Essays Res, 2019)
PURPOSE: Postprocedure epidural analgesia has a proven benefit over intravenous (i.v.) analgesia for pain management, but has not yet been demonstrated for uterine fibroid embolization (UFE). The objectives of this clinical audit were to determine if epidural patient-controlled analgesia (PCA) was beneficial to patient outcome as compared to i.v. PCA in decreasing parenteral opioid requirements and its associated side effects and determine if there is a difference in required oral opioids after the PCA is stopped. MATERIALS AND METHODS: This manuscript audited postprocedural pain management of 51 patients after UFE was performed. 20 patients received an i.v. PCA for post-UFE pain control and 31 received an epidural PCA for post-UFE pain control. Total hydromorphone dose, the frequency of anti-nausea medication use, the frequency of anti-pruritus medication use, and patient pain satisfaction data was collected. RESULTS: Total hydromorphone dose administered to patients post-UFE using epidural PCA was significantly less than patients using an i.v. PCA (P = 0.001). However, the frequency of nausea and pruritus between the two groups did not achieve statistical significance with (P = 0.663) and (P = 0.639) respectively. CONCLUSION: Our clinical audit found that parenteral opioid requirements administered after UFE can be significantly reduced by using epidural PCA instead of i.v. PCA. However, we found no statistically significant difference in medication related side effects or oral opioid use thereafter.